Analisis Kinerja Sistem Komunikasi SC-FDMA Pada Kanal Mobile To Mobile - Fitri Amillia; Mulyono Mulyono; Ade Putra Jaya (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
SC - FDMA is a modulation technique that uses a single carrier in the transmit data to be implemented on 4G uplink side. Channel model used in this system in the form of the channel model rayleigh fading mobile to mobile and mobile to fixed rayleigh fading. This study was to determine the performance of the system at the canal SCFDMA mobile to mobile . The modulation used QPSK, 16-QAM and 6-4QAM . The results showed first , the mobile channel to mobile rayleigh fading , performance SCFDMA communication system that has better performance , namely the QPSK modulation than the modulation 16- QAM or 64- QAM , with normalized Doppler frequency of 0.1 to 10-3 BER obtained EbNo about 24 dB . Second , the mobile channel to fix rayleigh fading , better performance , namely the QPSK modulation than the modulation 16- QAM or 64 -QAM , with normalized Doppler frequency of 0.1 to 10-3 BER obtained EbNo about 24 dB .Keywords: AWGN, Mobile to fix Rayleigh Fading, Mobile to mobile Rayleigh Fading, Modulation, SCFDMA